2018
DOI: 10.2147/cmar.s173740
|View full text |Cite
|
Sign up to set email alerts
|

Response of patients with locally advanced pancreatic adenocarcinoma to high-intensity focused ultrasound treatment: a single-center, prospective, case series in China

Abstract: PurposePatients with unresectable locally advanced pancreatic cancer (LAPC) are still in dire need of effective therapies. We performed this cohort study in order to assess the efficacy and safety of high-intensity focused ultrasound (HIFU) ablation in treating patients with unresectable LAPC.Patients and methodsEighty-seven cases with unresectable LAPC from January 2014 to December 2016 were finally recruited according to the inclusion criteria. The primary end point of our study was OS of all the cases, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
1
15
1
1
Order By: Relevance
“…There were fewer complications and side effects after tumor lesion ablation in the present study compared with previous reports (14,28,33,34,39,40). Meanwhile, no notable clinical symptoms and manifestations of mesenteric vascular occlusion, such as persistent abdominal pain and peritoneal irritation, were observed.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…There were fewer complications and side effects after tumor lesion ablation in the present study compared with previous reports (14,28,33,34,39,40). Meanwhile, no notable clinical symptoms and manifestations of mesenteric vascular occlusion, such as persistent abdominal pain and peritoneal irritation, were observed.…”
Section: Discussioncontrasting
confidence: 52%
“…It was first reported in 2000 that HIFU successfully ablates and treats pancreatic cancer (29). Several studies have confirmed the safety and efficacy of HIFU in the treatment of pancreatic cancer (10,(14)(15)(16)(19)(20)(21)(22)(23)(24)(25)(29)(30)(31)(32)(33)(34). The most common complications observed following HIFU treatment of pancreatic cancer include skin burns (10,15,17,(21)(22)(23)(30)(31)(32), pancreatitis (10,18,23,31,32), duodenal fistula (23,31) and obstructive jaundice (19,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25] Results from a meta-analysis showed that approximately 80% of patients with advanced PC who received HIFU therapy experienced pain reduction. 26 Ji et al 27 also reported that HIFU treatment was effective and the adverse events (AEs) associated with the treatment were rare and tolerable, especially for old patients and those with poor performance status. 28 Our previous study was also consistent with these results.…”
Section: Discussionmentioning
confidence: 99%
“…Cavitation then ensures and cell death occurs through the process of coagulative necrosis [14,15]. Previous studies have shown that HIFU treatment could treat, including but not limited to liver tumors and pancreatic cancer, and is associated with fewer serious adverse reactions [16,17]. According to our previous studies, HIFU treatment for primary liver cancer and colorectal liver metastases has achieved surprising positive results [18,19].…”
mentioning
confidence: 99%